The global shortage of essential drugs during the COVID-19 pandemic: Evidence based on aggregated media and social media reports - Mohammed Salahuddin; Dilshad Manzar; Aleem Unissa; Seithikurippu R Pandi-Perumal; Ahmed S BaHammam (Wolters Kluwer Medknow Publications, 2022)
Background: Implications from accumulated bodies of commentaries and media/social-media reports highlight the drug shortage during the COVID-19 pandemic. In this special report, the relation between drug shortage and response measures is discussed in the light of a preliminary data construct. Materials and Methods: Media reports and social media posts on public and national drug regulatory bodies' websites were searched between March 1, 2020, and August 11, 2020. The search's key terms were shortage, nonavailability, essential medicine, essential drug, imported medicine, imported drug, COVID-19, current pandemic, and corona. A qualitative and quantitative summary of drug-shortage response pages and trends of drug-shortage reports are presented. Results: In the developed countries, the drug regulatory bodies released drug-shortage response pages; such pages were not made available in the developing countries. There were reports of drug shortages from both the developing and developed countries. There were reports of drug shortage from as early as March 2020 when the lockdown was first implemented and continued until July 2020. The reported drug shortages varied from that of simple essential medicines to those needed in critical care. Conclusions: The study findings highlighted the spread (across the developing and developed countries), time trend of drug-shortage reports (started from the 1st week of the first round of lockdown and continued throughout the study duration), and nontermination of drug-shortage reports even after availability of drug-shortage response page.